TRENDS OF SERUM CREATININE LEVELS IN POST-OPERATIVE CORONARY ARTERIAL BYPASS GRAFT (CABG) PATIENTS; A CROSS SECTIONAL STUDY AT AFIC/NIHD RAWALPINDI - Naqvi, Shahab; Khan, Safdar Ali; Bakhsh, Muhammad; Javaid, Rehana; Zaida, Sabeen Khurshid (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess levels of serum creatinine pre and post operatively in CABG patients.Study Design: Descriptive cross sectional study.Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from June 2014 to Dec 2014.Material and Methods: Retrospective data of Forty three consecutive patients between age group of 25-70 years, who had undergone CABG  surgery in AFIC were enrolled in this study for investigation of serum creatinine levels. To asses trends of Serum creatinine levels, serum creatinine values were taken both preoperatively and post-operatively after every 24 hrs, 48 hrs, 72 hrs, 96 hrs.Results: A general trend of rise in serum creatinine is observed in post CABG patients with every 0.1 unit rise in every 24 hours. Similarly a fall in GFR is also seen in all post CABG patients.Conclusion: Serum levels of creatinine are found raised in post CABG patients with a fall in glomerular filtration rate (GFR).